TANGGUNG JAWAB HUKUM SEKTOR LISTRIK ATAS KERUSAKAN EKOSISTEM HUTAN DALAM PROYEK-PROYEK STRATEGIS NASIONAL: Studi tentang Hukum Pidana Lingkungan Hidup dan Akuntabilitas Perusahaan - Eko Pratama; La Ode Husen; Azwad Rachmat Hambali; Muhammad Kamran (CV. AFDIFAL MAJU BERKAH, 2026)
National Strategic Projects (NSPs) in the electricity sector play an important role in supporting national energy needs and economic growth. However, the implementation of these projects frequently causes damage to forest ecosystems, resulting in environmental degradation and disruption of forest ecological functions. This study aims to analyze the forms of criminal liability in the electricity sector for forest ecosystem damage arising from the implementation of NSPs. The research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that criminal liability may be imposed on both corporations and individuals through the application of the principles of strict liability and vicarious liability, particularly in cases involving violations of environmental and forestry regulations. Criminal law enforcement still faces several obstacles, including regulatory disharmony, difficulties in proving causality, and the justification of actions in the name of national development. Therefore, regulatory harmonization and stronger law enforcement oriented toward sustainable development principles are necessary to ensure effective protection of forest ecosystems.